Study on the Method for Measuring Stress on Rock Mass Excavation Surface under Extremely High Stress Conditions. (12th October 2022) - Ai, Kai; Zhang, Xinhui; Zhou, Chao
Abstract : In view of the limitations of several existing stress measurement methods under extremely high stress conditions (stress − strength ratio σ / R c > 0.5 ), this paper proposes a slot relief method based on partial deformation recovery to measure rock mass surface stress under extremely high stress conditions and justifies its viability with the help of an infinite element model. This method is then used to measure and study a research tunnel in West China's Jinping II Hydropower Station, where the maximum stress measured reached 80 MPa. In the process of measurement, this method needs neither complete borehole core nor ultrahigh pressure equipment. On the contrary, the test equipment is easy to carry and operate on, suitable for rock mass surface stress measurement under extremely high stress conditions, and able to provide in situ stress measurements for cavern rockburst prevention and slope management.